An integrated techno-economic and life cycle environmental assessment of power-to-gas systems. (1st May 2017) - Parra, David; Zhang, Xiaojin; Bauer, Christian; Patel, Martin K.
Graphical abstract: Highlights: A PEM electrolyser only accounts for up to 25% of the total levelized cost. P2H offers lower environmental impacts than conventional production in most scenarios. P2H and P2M must use clean electricity in order to provide environmental benefits. Biogas upgrading reduces the environmental impacts by 2–9% regarding CO2 capture. Increasing system scale improves both economic and environmental performance. Abstract: Interest in power-to-gas (P2G) as an energy storage technology is increasing, since it allows to utilise the existing natural gas infrastructure as storage medium, which reduces capital investments and facilitates its deployment. P2G systems using renewable electricity can also substitute for fossil fuels used for heating and transport. In this study, both techno-economic and life cycle assessment (LCA) are applied to determine key performance indicators for P2G systems generating hydrogen or methane (synthetic natural gas – SNG) as main products. The proposed scenarios assume that P2G systems participate in the Swiss wholesale electricity market and include several value-adding services in addition to the generation of low fossil-carbon gas. We find that none of the systems can compete economically with conventional gas production systems when only selling hydrogen and SNG. For P2G systems producing hydrogen, four other services such as heat and oxygen supply are needed to ensure the economic viability of a 1 MW P2H system. CO2 captured from the air adds $50/MW ht of extra levelised cost to SNG compared to CO2 supplied from biogas upgrading plants and it does not offer an economic case yet regardless of the number of services. As for environmental performance, only the input of "clean" renewable electricity to electrolysis result in environmental benefits for P2G compared to conventional gas production. In particular, more than 90% of the life cycle environmental burdens are dominated by the electricity supply to electrolysis for hydrogen production, and the source of CO2 in case of SNG.